Tr-Span of Directed Wheel Graphs - Besson Marc (Discussiones Mathematicae Graph Theory, 2018)
In this paper, we consider T-colorings of directed graphs. In particular, we consider as a T-set the set Tr = {0, 1, 2, . . ., r−1, r+1, . . .}. Exact values and bounds of the Tr-span of directed graphs whose underlying graph is a wheel graph are presented.